Iodine promoted iodosulfonylation of alkynes with sulfonyl hydrazides in an aqueous medium: highly stereoselective synthesis of (E)-β-iodo vinylsulfones. (26th April 2018) - Hou, Yunlei; Zhu, Liangyu; Hu, Hao; Chen, Shaowei; Li, Zefei; Liu, Yajing; Gong, Ping
Abstract : An efficient, molecular iodine-promoted MCR of alkynes and sulfonyl hydrazide for the synthesis of ( E )-β-iodo vinylsulfone derivatives has been developed. Abstract : A catalyst-free and metal-free sulfonylation reaction for the preparation of ( E )-β-iodo vinylsulfones from alkynes with sulfonyl hydrazides and molecular iodine was efficiently developed under mild and environmentally benign conditions, in water without any ligand or catalyst. The reaction gave a range of structurally diverse β-iodo vinylsulfones with excellent E selectivities and high yields.